Judgment, Imagination and the Search for Justice - Roger W. H. Savage (Études Ricoeuriennes / Ricoeur Studies, 2016)
The multiplicity of demands and claims in ultra-pluralistic societies complicates the search for justice. Furthermore, the normative force of competing ideals gives rise to an aporia at the heart of the idea of justice’s federating force. In this article, I argue that exemplary moral and political acts evince these ideals by reason of their fittingness with respect to the demands of the situations to which they respond. As such, these acts lay claim to their normative value by exemplifying the “rule” that each act summons. Drawing upon aesthetic experience’s lateral transposition onto the planes of ethics and politics, I show how imagination is operative in practical judgments (phronesis). Accordingly, I relate the search for justice to an eschatology of non-violence, which for Paul Ricœur takes the place of the critique of ideology in its opposition to an ontology of lingual understanding.